Fish oil – how does it reduce plasma triglycerides? - Shearer, Gregory C. (2011)
Long chain omega-3 fatty acids (FAs) are effective for reducing plasma triglyceride (TG) levels. At the pharmaceutical dose, 3.4 g/day, they reduce plasma TG by about 25-50% after one month of treatment, resulting primarily from the decline in hepatic very low density lipoprotein (VLDL-TG) production, and secondarily from the increase in VLDL clearance. Numerous mechanisms have been shown to contribute to the TG overproduction, but a key component is an increase in the availability of FAs in the liver. The liver derives FAs from three sources: diet (delivered via chylomicron remnants), de novo lipogenesis, and circulating non-esterified FAs (NEFAs). Of these, NEFAs contribute the largest fraction to VLDL-TG production in both normotriglyceridemic subjects and hypertriglyceridemic, insulin resistant patients. Thus reducing NEFA delivery to the liver would be a likely locus of action for fish oils (FO). The key regulator of plasma NEFA is intracellular adipocyte lipolysis via hormone sensitive lipase (HSL), which increases as insulin sensitivity worsens. FO counteracts intracellular lipolysis in adipocytes by suppressing adipose tissue inflammation. In addition, FO increases extracellular lipolysis by lipoprotein lipase (LpL) in adipose, heart and skeletal muscle and enhances hepatic and skeletal muscle β-oxidation which contributes to reduced FA delivery to the liver. FO could activate transcription factors which control metabolic pathways in a tissue specific manner regulating nutrient traffic and reducing plasma TG.